2020
DOI: 10.1021/acsapm.9b01201
|View full text |Cite
|
Sign up to set email alerts
|

Green, Low-Cost, User-Friendly, and Elastomeric (GLUE) Microfluidics

Abstract: Micro total analysis systems (μTAS) are highly attractive across numerous fields including science, engineering, and medicine due to their portability, low power use, and efficient sample and reagent consumption. Development of fully functional microfluidic devices is based on iterative design and testing of multiple prototype microdevices, and the use of hazardous conventional microfabrication methods makes this iterative process resource-intensive and prohibitive for many users worldwide. Rapid prototyping t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…[30] The interest in this methodology increased in recent years since some authors have been successfully applied methods using commercial microwave ovens to achieve fast PDMS curing envisaging microfluidic applications. [31][32][33] The silicone used in this study is cross-linked by Ptcatalysed hydrosilylation reaction, that is, carried out at Si H bonds have an exponential increase when the temperature is raised from 55 C to 75 C; the reaction is completed in nearly 5 minutes, as reported by Bhattacharya and coworkers. [34] Therefore, it is reasonable to state that that PDMS crosslinking can be completed within 10 minutes, as observed in this study and that the process is accelerated by the heating effect provided by microwave irradiation.…”
Section: Silicone/pmma Blends Characterizationmentioning
confidence: 61%
See 1 more Smart Citation
“…[30] The interest in this methodology increased in recent years since some authors have been successfully applied methods using commercial microwave ovens to achieve fast PDMS curing envisaging microfluidic applications. [31][32][33] The silicone used in this study is cross-linked by Ptcatalysed hydrosilylation reaction, that is, carried out at Si H bonds have an exponential increase when the temperature is raised from 55 C to 75 C; the reaction is completed in nearly 5 minutes, as reported by Bhattacharya and coworkers. [34] Therefore, it is reasonable to state that that PDMS crosslinking can be completed within 10 minutes, as observed in this study and that the process is accelerated by the heating effect provided by microwave irradiation.…”
Section: Silicone/pmma Blends Characterizationmentioning
confidence: 61%
“…[ 30 ] The interest in this methodology increased in recent years since some authors have been successfully applied methods using commercial microwave ovens to achieve fast PDMS curing envisaging microfluidic applications. [ 31‐33 ]…”
Section: Resultsmentioning
confidence: 99%
“…However, these methods are suitable for manipulating droplets but not for massive droplet generation to meet digital immunoassays. The passive method generates droplets by adjusting the flow rate and channel structure, mainly including T-channel [ 267 , 268 ], flow focusing [ 145 , 269 ], and coaxial flow focusing [ 270 , 271 ]. Conventional droplet assays can generate a mass of monodisperse droplets but with low throughput.…”
Section: Luminescence Immunoassays On Microfluidic Chipsmentioning
confidence: 99%
“…They did several experiments successfully as proof of concept such as rapid protein detection etc. Speller et al [ 30 ] reported a green technique for rapid prototyping of a 3D polydimethylsiloxane (PDMS)-based microfluidic structure using white glue with minimum widths of 200 μm and adjustable heights. A tabular representation depicting the historical evolvements of green materials for fabricating the basic structure of GGLOC is shown in Table 1 .…”
Section: Green Pathways For Graphene-based Locmentioning
confidence: 99%